Detecting myasthenia gravis as a cause of unclear dysphagia with an endoscopic tensilon test. (August 2021) - Warnecke, Tobias; Im, Sun; Labeit, Bendix; Zwolinskaya, Olga; Suntrup-Krüger, Sonja; Oelenberg, Stephan; Ahring, Sigrid; Schilling, Matthias; Meuth, Sven; Melzer, Nico; Wiendl, Heinz; Ruck, Tobias; et al.
Aims: The flexible endoscopic evaluation of swallowing-tensilon test (FTT) was developed to diagnose myasthenia gravis (MG) in patients with unclear pharyngeal dysphagia. The purpose of this study was to determine sensitivity and specificity of the FTT and compare its diagnostic validity with that of other diagnostic markers. Methods: In this single-centre pragmatic clinical cohort study, a total of 100 patients with unclear pharyngeal dysphagia were eligible to undergo FTT. All patients were subjected to FTT and subsequently followed up clinically. FTT was considered positive if a significant improvement of pharyngeal swallowing function could be objectified endoscopically upon administration of edrophonium chloride. In addition, repetitive nerve stimulation test and serum MG antibody analysis were conducted. Results: All subjects (mean age 62.5 ± 14.1 years, female 33) underwent FTT without any complications. According to the results of the diagnostic procedures and based on long-term clinical follow-up for at least 3 years, 51 patients were finally diagnosed with MG. The sensitivity and specificity for the FTT was 88.2% and 95.9%, respectively. Application of the Cochran's Q test showed statistically significant heterogeneity among the diagnostic tests, with results indicating FTT performance to be more accurate than the repetitive nerve stimulation results ( p < 0.001) and comparable with serum antibody tests ( p > 0.99). Conclusion: FTT has excellent clinical properties to be used routinely in the assessment of dysphagia with isolated or predominant pharyngeal muscle involvement allowing rapid and accurate diagnosis of MG.